O peso das mochilas de escolares de 10 a 15 anos de uma escola pública no Paraná - Jorge Alan Glass; Maria das Graças Anguera (Universidade Estadual do Oeste do Paraná, 2015)
Some health studies highlight that postural changes and backaches school 10 to 15 years are caused by excess weight in their backpacks. The aim of study was to determine whether the weight of the backpacks used by school between 10 and 15 years of Public School of Paraná is appropriate, acceptable or inappropriate according to their body mass, suggested by the scientific community and established by Law 17,482/2013. The checking the adequacy of the backpack weight in relation to body mass was made according to two parameters: one using the classifications suggested by the scientific community: adequate (≤10% of body weight of the subject); acceptable (≤15% of the body weight of the subject); inadequate (>15% of the body weight of subject) and other parameters using the classifications suggested by Law 17,482/2013: appropriate (≤10% of the body weight of the subject) and inappropriate (>10% of the body weight of the subject). The results of this study showed that when asked averages grouped by age, neither group was inappropriate as the literature of the parameters that is up to 15% transported weight of body mass, however, according to Law 17,482/2013, four of six age groups were inadequate, being 10, 11, 12 and 14 years. There is a very significant difference when comparing the two references analysis as to evaluate the outcome of the proposal of the authors, most of the weights of the investigated backpacks is in adequate and acceptable standards, which together account for almost 90% of the sample, and when analyzing the results from the Law 17,482, prevails inadequate standard.